Statins use amidst the pandemic: prescribing, dispensing, adherence, persistence, and correlation with COVID-19 statistics in nationwide real-world data from Poland - Kardas, Przemysław; Kwiatek, Angelika; Włodarczyk, Piotr; Urbański, Filip; Ciabiada-Bryła, Beata (Frontiers in Pharmacology, 2024)
Background: Adherence to medications presents a significant challenge in healthcare.Statins, used in primary and secondary prevention of cardiovascular disease, are of particular importance for public health. The outbreak of the COVID-19 pandemic resulted in additional healthcare system-related barriers impeding the execution of therapies. This study aimed to assess the use of as well as adherence and persistence to statins in a national cohort of 38 million of Polish citizens during pandemic. Methods: A retrospective analysis of prescription and dispensation data for all statins users from the national payer organization covering the years 2020-2022 was conducted.Medication adherence was assessed using the Medication Possession Ratio, for persistence the 30-days cut-off was accepted. National data on COVID-19 cases and COVID-19 related deaths were obtained from ECDC.Results: The analysis identified 7,189,716 Polish citizens (approximately 19% of Polish population) who were dispensed at least 1 pack of statins within the study period. Over that time, there was a continuous significant increasing trend in prescribing and dispensing of statins. Despite a total increase of 18.9% in the number of prescribed tablets, the percentage of tablets dispensed remained similar, averaging 86%. Overall percentage of adherent patients was 48.2%. For a random sample of 100,000 patients, the mean period of continuous therapy in 2022 was 6.2 +/-5.3 months. During the lockdown period, the mean number of prescribed and dispensed tablets was lower by 6.8% and 5.9%, respectively (P<0.05). However, fluctuations in the number of COVID-19 cases or COVID-19-related deaths per week had no major impact on the prescribing and dispensing of statins.Conclusions: Over the time of pandemic, there was a continuous increase in the number of statin tablets prescribed and dispensed in Poland. This suggests that, despite the potential limitations posed by COVID-19, access to statins remained easy, which may be attributed to the mass-scale implementation of the national e-prescription system. However, it is crucial to realise that approximately 1/7 of prescribed statin doses were never dispensed, and the overall levels of adherence and persistence were low. This underscores the necessity for concerted efforts to change this scenario in Poland.